Połączenia Klejone Elementów Stalowych w Konstrukcjach Budowlanych i Mostowych - Czudek, H. (Engineering Transactions, 1965)
The present paper is devoted to problems of glue selection for metals that may find application in the construction of steel bridges in Poland. It gives also. some information on the technique of glued joints of steel. Home produced epoxy glues are discussed in particular. The author presents also some results of static and fatigue tests of glued joints of steel elements. As a result of an analysis of the drawbacks and advantages of glued joints a tentative method is proposed for the determination of the applicability range of the glued joints in the construction of steel bridges, Problems connected with the strength analysis of a glued joints are considered in brief, the phenomenon of creep and ageing of glues being pointed out. Problems of dimensioning glued joints of steel elements subjected to shear are treated in greater detail. The problem of dimensioning such joints is considered for an epoxy glue. An empirical method for dimensioning the joints is proposed for the case in which not one but a set of glues are prescribed. This method enables the obtainment from the mechanical conditions of not only the glued area but also the type of glue satisfying the conditions of the problem. Finally, the paper contains some information on the construction of a prototype steel bridge span with glued joints.